Reconciling the individual and societal level in comparative cultural analysis: An archetypal analysis of values and norms across 76 countries - Juliette de Wit; Sjoerd Beugelsdijk (Global Labor Organization (GLO), 2024)
Despite the continued popularity of cross national culture research across social sciences, the use of multidimensional value based models is not without discussion. A key issue concerns the observation that value diversity within countries may be larger than between countries, giving rise to a theoretical and empirical tension between the national cultural level and the individual level. This paper examines the individual and national cultural level simultaneously using a novel typology of norms and values. Leveraging pooled World Values Survey and European Values Study data of 137,505 individuals that live in 76 countries across the world, we find three archetypes that capture individuals' values and norms in a cross-country setting. Each individual is characterized by a configuration of archetypes. Findings illustrate that each archetype is associated with different socio-economic demographics. Moreover, we observe marked differences between the probability of finding any of the three individual archetypes in a country. The paper illustrates how a typological approach can advance our understanding of cultural differences across countries, while acknowledging individual level value diversity.
Keywords: D02; P50; Z13; 330; values; norms; international comparison; culture; archetype; typology